HYDROGEOLOGICAL CONDITIONS AND GROUNDWATER QUALITY IN VAGIA BASIN (VIOTIA/GREECE) - Stamatis, G.; Davou Ι.; Hermides, D.; Karavitis, C. (Bulletin of the Geological Society of Greece, 2016)
This study refers to hydrogeological conditions that dominate in the closed basin of Vagia of Viotia with emphasis on groundwater quality. It highlights the environmental problem of the region, associated with floods, phenomenon which occurs every year and lasts throughout the wet season. This, results in flushing undesirable substances from the territories of intensely cultivated area and the penetration into the groundwater of Neogene- Quaternary and carbonates aquifers. Qualitative charge of groundwater is reflected in the high concentrations of the ions Na+:22,2-133,4 mg/l, K+:0,3-12,0mg/l, SO4 2-:2,1-68,9mg/l, Cl-:24,8-241,1mg/l, NO3-:13,6-67,0mg/l, NH4 +:0,01-1,75mg/l, PO43-:0,03-0,94mg/l as well as the strong presence of heavy metals (Fe, Mn, Zn, Ni, Co, Cu and Cr). Qualitative charge of groundwater is attributed to natural (geogenic) and anthropogenic factors.